Designing Information Systems for Small and Medium Enterprises Based on Application - Rachmanto, Adi; Gunawan, A; Setiawan, S; Sofiane, H (Universitas Komputer Indonesia, 2024)
Small and medium enterprises are a major factor in playing a role in the era of globalization to advance the country's economy. On the other hand, there are still many small and medium enterprises that still apply information systems manually, which is an obstacle in the world of business competition. Therefore, the need for a transaction application that facilitates sales activities, which are still manually digital. So the purpose of this study is to design transaction applications for small and medium enterprises with the latest information systems. To support this research, researchers used a descriptive method approach with a practical and applicable approach by collecting data using literature studies and developing information systems using a prototype method with an object-based approach. The results show that this design has an impact on changes in business performance. because in this application provides the latest features and is easy to operate by small and medium businesses. Some of the features include: Login Menu, Main Menu, Item Menu and Sales Menu. Basically, with some far better benefits provided, many small business operators are reluctant to use them for reasons related to equipment costs. It can be concluded that in designing an application well, the resulting application will run well. This application is useful for reducing the occurrence of small errors in transactions